Investigating the synthesis parameters of durian skin-based activated carbon and the effects of silver nanocatalysts on its recyclability in methylene blue removal - Amir, Dzilal; Nasaruddin, Ricca Rahman; Yousefi, Maryam; Mastuli, Mohd Sufri; Sulaiman, Sarina; Alam, Md. Zahangir; Engliman, Nurul Sakinah (Springer Science+Business Media, LLC, 2024)
Activated carbon (AC) is the most common and economically viable adsorbent for eliminating toxic organic pollutants, particularly dyes, from wastewater. Its widespread adoption is due to the simplicity and affordable production of AC, wherein low-cost agricultural wastes, such as durian skin can be used. Converting durian skin into AC presents a promising solution for its solid waste management. However, inherent drawbacks such as its non-selectivity, relatively short lifespan, and laborious replacement and recovery processes diminish the overall efficacy of AC as an adsorbent. To address these challenges, the immobilisation of metal nanocatalysts such as silver nanoparticles (AgNPs) is one of the emerging solutions. AgNPs can facilitate the regeneration of the adsorption sites of AC by catalysing the conversion of the adsorbed dyes into harmless and simpler molecules. Nevertheless, the immobilisation of AgNPs on AC surfaces can be challenging as the pore-size formation of AC is hard to control and the nanomaterials can easily leach out from the AC surface. Hence, in this study, we synthesised AC from durian skin (DS) and immobilised AgNPs on the AC-DS surface. Then, we used methylene blue (MB) removal for studying the adsorption capability and recyclability of the AC-DS. In the synthesis of AC-DS, the influences of reaction temperature, activating agent, and acid-washing to its capability in adsorptive removal of MB in solution were first determined. It was found that 400 °C, KOH activating agent and the presence of acid-washing (50% of HNO3) resulted in AC-DS with the highest percentage of MB removal (91.49±2.86%). Then, the overall results from three recyclability experiments demonstrate that AC-DS with immobilised AgNPs exhibited higher MB removal after several cycles (up to 6 cycles) as compared to AC-DS alone, proving the benefit of AgNPs for the recyclability of AC-DS. We also found that AgNPs/Citrate@AC-DS exhibited better adsorption capability and recyclability as compared to AgNPs/PVP@AC-DS indicating significant influences of type of stabilisers in this study. This study also demonstrates that the presence of more oxygen-containing functional groups (i.e., carboxyl and hydroxyl functional groups) after acid-washing on AC-DS and in citrate molecules, has a greater influence on the performance of AC-DS and AgNPs/Citrate@AC-DS in the removal of MB as compared to the influences of their BET surface area and pore structure. The findings in this study have the potential to promote and serve as a guideline for harnessing the advantages of nanomaterials, such as AgNPs, to enhance the properties of AC for environmental applications.